Farm Production Diversity in Aquaculture Has Been Overlooked as a Contributor to Sustainability - Johnson, Mark P. (Frontiers in Sustainable Food Systems, 2021)
Like many sectors, the expansion of aquaculture has issues related to sustainable resource use and environmental change. These challenges are widely recognised and are addressed with sectoral strategies. Even when culturing a single species, the specifics of impacts, constraints and pressures are likely to vary in effects for different farm types. On the other hand, production efficiencies can drive farms towards homogeneity. A simple model is used in this study to demonstrate farm-scale budgets and the pressure to intensify production towards an optimum. A range of interventions can provide incentives for less intensive production: these include price premiums and altered cost bases. Integrated multitrophic aquaculture (IMTA) does not offer a route to less intensive production systems if the productivity of the extractive species (e.g., algae) is linked to the intensity of the fish farm, although alternative incentives for IMTA are possible. Increases in the intensity of production (as stocking density) can be mitigated by increasing farm capacity. An expanded production model suggests that this will lead to larger farms at relatively high stocking densities. Where farms are subject to variable economic and biological processes, this can lead to some combinations of intensity and capacity to have less variable earnings than others. The promotion of diverse aquaculture sectors may allow some of the ecological and social synergies available to smaller farms to be combined at a regional scale with the greater production of large farms. Cost, price and/or regulatory incentives are needed to create diverse production systems.